2021
DOI: 10.3389/fendo.2021.583654
|View full text |Cite
|
Sign up to set email alerts
|

Modern India and Dietary Calcium Deficiency—Half a Century Nutrition Data—Retrospect–Introspect and the Road Ahead

Abstract: Calcium and vitamin D are inseparable nutrients required for bone health. In the past half a century, the dietary calcium intake of rural, tribal, and urban India has declined. Though India is the largest producer of milk and cereals, the major source of calcium in India is through non-dairy products. The highest intake of cereals and lowest intake of milk & milk products was observed in rural and tribal subjects whereas, the intake of cereals, milk & milk products were similar in both urban an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…The current study shows that 59.9% (95% CI, 58.0–62.0) of study participants had calcium levels below 10 mg/dl and 39.7% (95% CI, 38.0–42.0) had Vitamin D levels below 12 ng/ml. This is consistent with the finding that about 80–85% of Indian population is suffering from various degrees of vitamin D deficiency (VDD) [ 56 ]. Various studies, in contrast to our study, have reported prevalence of VDD ranging from 88.6% to 93.0% [ 19 21 ], although these were small studies conducted in a particular geography.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study shows that 59.9% (95% CI, 58.0–62.0) of study participants had calcium levels below 10 mg/dl and 39.7% (95% CI, 38.0–42.0) had Vitamin D levels below 12 ng/ml. This is consistent with the finding that about 80–85% of Indian population is suffering from various degrees of vitamin D deficiency (VDD) [ 56 ]. Various studies, in contrast to our study, have reported prevalence of VDD ranging from 88.6% to 93.0% [ 19 21 ], although these were small studies conducted in a particular geography.…”
Section: Discussionsupporting
confidence: 92%
“…Childhood and adolescence are crucial period for skeletal mineralization. Nutritional trends from independence (1947) to recent years (2016) shows that there is a consistent gap between the production and consumption of dietary calcium in Indian dietary pattern [ 56 ]. The current study shows that 59.9% (95% CI, 58.0–62.0) of study participants had calcium levels below 10 mg/dl and 39.7% (95% CI, 38.0–42.0) had Vitamin D levels below 12 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium also played the protective role in the treatment of essential hypertension (Liu et al, 2020;Nadal et al, 2018) and prevention of colon cancer (Gutierrez et al, 2019). Some scholars have conducted long-term researches on the role of calcium in the human body, and consistently pointed out that people with white, yellow or dark skin were threatened by calcium deficiency throughout their lives (Balk et al, 2018;Harinarayan et al, 2021). It was difficult for Chinese people to obtain the dietary calcium intake (DRIS) recommended by the Chinese Nutrition Society in the daily diet (Ge & Chang, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the greater proportion of milk production in rural India as compared to urban regions, rural-dwelling individuals consume less milk and milk products. [ 17 ] Therefore, it is prudent that regular supplementation of calcium and vitamin D be done in addition to encouraging more consumption of calcium from dietary sources. Long-term measures like food fortification may be a definite solution to combat the endemicity of vitamin D deficiency.…”
mentioning
confidence: 99%